Analisis Ketahanan Hidup Pasien Kanker Paru Menggunakan Regresi Weibull - Arivatus Solehah; Mohamat Fatekurohman (Universitas Sebelas Maret, 2018)
Lung cancer is one of the diseases which difficult to detect because of uneasy symptoms detection till it develops being the risky one. But, if the disease has been found, it can spread fast and cause death. According to the data of WHO, the type of cancer which causes the most of death is lung cancer which reaches 1,3 milion death per year. Therefore, a survival analysis will be conducted to determine factors that affect the survival of lung cancer patient by using Weibull regression. The result shows some factors that significantly influence the survival of lung cancer patient are gender, erythrocyte, and general condition. Keywords : lung cancer; survival analysis; Weibull regression